FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KINERJA PEGAWAI PADA RUMAH SAKIT UMUM ARIFIN NU’MANG RAPPANG KABUPATEN SIDENRENG RAPPANG - Misbahuddin Misbahuddin (Jurnal Bisnis dan Kewirausahaan, 2019)
The performance of employees, especially nurses, is a strategic and most important thing for hospital development.Purpose and Objectives of this study to determine the factors that influence the performance of employees at Arifin Nu'mang General Hospital Rappang, Sidrap Regency, South Sulawesi Province.The research design model used was descriptive analytic with cross sectional approach, with a total sample of employees (nurses) of 40 people, determination of sample size using simple random sampling.Data collection using a questionnaire. Data processing using IBM computers with SPSS program version 21.0 is presented in narrative and table form. The statistical test used was Chi-Square with significance level α = 0.05.The results of the study showed that the performance of the categorized employees was sufficient at 57.5%. In the bivariate analysis factors related to nurse performance are leadership, work discipline.Based on the results of this study indicate that the most influential factor on employee performance at Arifin Nu'mang hospital is work discipline